âBATIK MBANTULANâ DI SENTRA BATIK GIRILOYO DAN WIJIREJO BANTUL - dan Arif Suharson, I Made Sukanadi (CORAK, 2012)
The study of batik in the batik centers of Giriloyo and Wijirejo Bantul is intended to develop the existing motifs of batik mbantulan and create new motifs while maintain the identity of batik mbantulan with its local-rich characteristics in Kabupaten Bantul. The development of batik mbantulan has undergone the rising and falling trend. To survive and develop artisans of batik mbantulan have to adapt themselves to the ongoing market preference through the improved characteristics of batik mbantulan. It is necessary to explore the possible existing motifs of batik mbantulan that have brought up the batik center of Giriloyo and Wijirejo have. The motifs of batik mbantulan have to be reserved in the batik products through identification, diversification, and creation of new batik mbantulan motifs, Therefore, the new designs is expected to be more competitive in batik market and create the spirit of creativity and innovativeness among the artisans of batik mbantulan in the Batik Center of Giriloyo and Wijirejo Bantul. The main obstacles that the artisans in the batik center of Giriloyo and Wijirejo have to face up is the meeting of consumersâ orders with their new motifs. The artisans are not capable enough to create new designs through the development of mbantulan motifs and prefer to work on the present and general motifs of batik Yogyakarta. The study is expected to deal with the artisansâ problem in creating new designs / motifs and improve their capacity to make new creative and innovative designs to meet consumersâ desired standard. In turn, this will lead to a better economic prospect for the artisans of batik mbantulan in the batik center of Giriloyo and Wijirejo. Key words: batik mbantulan, artisans, motifs